Analysis of N-nitrosodiprophylamines Carcinogenic Compound in Meat-Processing using Headspace-Single Drop Microextraction-Gas Chromatography-Flame Ionization Detector (HS-SDME-GC-FID) - Teguh Hari Sucipto; Ganden Supriyanto; Yanuardi Raharjo (IPTEK Journal of Proceedings Series, 2015)
Analysis of N-nitrosodiprophylamines carcinogenic compound in processed meat especially hamburger and kebab had occured by HS-SDME-GC-FID technique. The results were obtained determining the optimum pH was 4, the optimum stirring speed was 6 scale, and the temperature of extraction was 30 ºC. It was obtained in this study that the detection limit of 78 ppb, the percent recovery of 101,18%, precision between 0,089% to 0,566%, and the true enrichment factor was 3372,66 times. From the results of the study was concluded that HS-SDME-GC-FID technique can be used to analyze the carcinogenic compound N-nitrosodiprophylamines (NDPA) found in meat-processing (hamburger and kebab) by the concentration of each samples as follows, hamburger I of 0,27 ppm, hamburger II of 0,73 ppm, hamburger III of 1,39 ppm, and kebab I of 3,13 ppm